EFEK VARIASI WAKTU BALL MILLING TERHADAP KARAKTERISTIK ELEKTROKIMIA SEL SUPERKAPASITOR BERBASIS KARBON - Fitria Puspita Sari; Erman Taer; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Supercapacitor electrodes from  rubber wood saw dust (RWSD) have been fabricated using experiment method to study the ball milling  variation time  on performance of the supercapacitor cells. The carbon electrodes were prepared with time variation of  20, 40, and 80 hours and thickness  of  0.2 mm.  Carbon  electrodes were carbonized at 600oC and  followed by  physical activation  method in  CO2  gas atmosphere  on the constant temperature of 900o C, and chemical activation was performed by  KOH as an activating  agent. Densities  of the electrodes were  0.849 g/cm3 , 0.892 g/cm3 , 0.982 g/cm3 respectively. XRD measurement showed the peaks of carbon  electrodes at 2θ of 24.091o and  44.473o which represented  the presence of carbon  materials  with their crystal orientation of (002) and (100). SEM micrograph  on  magnification of 1000X showed that the pore  distribution of the carbon  electrodes dominant on macropores. This study found that the effects  of  increasing  of  ball milling  time  influenced  the electrochemical properties of  supercapacitor electrodes fro m RWSD.  The optimum  supercapacitor performance was found on  20 hour  milling time  electrode  and had a specific capacitance of 55.414 F/g.